Introducing a new classification for drug-induced sleep endoscopy (DISE): the PTLTbE system - Veer, Vik; Zhang, Henry; Mandavia, Rishi; Mehta, Nishchay (Sleep & breathing, 2020)
Purpose A new classification system is proposed to help the interpretation of drug-induced sleep endoscopy (DISE). The purpose is to create a classification system that improves upon existing systems designed to assess suitability of lateral wall surgery such as expansion pharyngoplasty whilst improving the reliability of the classification. Methods A qualitative study into the difficulties trainees had with existing systems was used to identify key issues that needed to be addressed. A visual description of the palate, tonsils, lateral pharyngeal wall, tongue base, epiglottis (PTLTbE) classification was developed. Preliminary data on the inter-rater reliability of PTLTbE were collected. Twenty junior doctors were asked to interpret 5 DISE videos using the PTLTbE classification, and the kappa and percentage agreement were calculated. Results The Krippendorff alpha ranged between 0.56 and 0.86 for individual DISE videos which compared favourably with the results from those who also completed the VOTE classification (range 0.31 to 0.66). The overall percentage agreement for PTLTbE was 90.1%. Conclusions There are a number of advantages of the PTLTbE system over other existing DISE classifications. (1) Tonsillar obstruction is separated from lateral pharyngeal wall collapse. (2) Interobserver reliability is improved, critical to improve communication, patient outcomes and future research. (3) The learning curve to use this system is short. Most doctors did not need to refer to the classification images as an aide-memoire after a few uses of the PTLTbE system. A fuller examination of the reliability of the PTLTbE system is underway along with examination of its use in clinical settings.